Identifikasi Metabolit Bioaktif pada Asam Jawa (Tamarindus indica L.) menggunakan Komputasi Dinamika Molekuler untuk Penargetan HER-2 Kanker Payudara - Ramadhan, Dwi Syah Fitra; Indraswari, Ni Luh Astri; Hakim, Supartina; Rusli, Rusli; Nurisyah, Nurisyah; Asikin, Asyhari; Fakih, Taufik Muhammad; Aksar, M (Program Studi Farmasi Universitas Mandala Waluya, 2024)
The HER-2 (Human EGF Receptor-2) receptor is a receptor known to be strongly correlated with carcinogenesis and a worse prognosis in breast cancer patients. One of the native Indonesian plants that has been reported to inhibit breast cancer growth is tamarind (Tamarindus indica L.) which is known to contain various active metabolites. However, until now, the molecular activity of each of these metabolites has not been known. and one of the highly accurate simulation methods commonly used is molecular dynamics simulation. This study aims to understand the binding stability of active metabolites in tamarind computationally using molecular dynamics. The simulation begins with the preparation of 3D structures of ligands and receptors. The ligand of active metabolite from tamarind tree was obtained from KnapSack natural compound database, and the 3D structure of HER-2 receptor was obtained from PDB site with code 3PP0 and resolution of 2.25 Å. Furthermore, molecular tethering was performed using Autodock4 software. A high-performance computer was used for molecular dynamics simulation with Gromacs 2016 software for 100 nanoseconds (ns). Afterwards, molecular affinity analysis was performed, including RMSD (Root Mean Square Deviation) and RMSF (Root Mean Square Fluctuation). The analysis results showed that of the 6 compounds found in tamarind plants, the orientin compound showed the most favorable molecular Tethering activity with a value of -8.41 Kcal/mol. Although still higher than the natural ligand, the value is close to the value of the natural ligand with a difference of 1.8 Kcal/mol, which is -10.21 Kcal/mol. Furthermore, orientin showed very similar stability to the native ligand, as observed from the RMSD and RMSF analysis. In conclusion, the compound orientin found in tamarind has the potential to be a lead compound for inhibiting HER-2 in breast cancer.